THE DETERMINATION OF PRODUCTION AND DISTRIBUTION POLICY IN PUSH-PULL PRODUCTION CHAIN WITH SUPPLY HUB AS THE JUNCTION POINT - BULAN ASTRID THERESIA (NIM 23416041), CITRA
The development of technology causes the needs of products and services become increasingly complex, diverse, and fluctuating. This causes the level of inter-company dependencies within a production chains increased. To be able to compete, efficiency improvements need to be done collaboratively in the production chain network. One of the efforts to improve the efficiency of the production chain is to harmonize production and distribution activities. PT AHM is a motorcycle manufacturer in Indonesia. PT STLJ is one of the suppliers of PT AHM spare parts. Currently, PT STLJ has high inventory amount. The high inventory of PT STLJ is due to the safety stock contract with PT AHM that requiring PT STLJ to keep the safety stock of 3 (three) times the number of demand. The roots of problem behind the establishment of the safety stock contract are the tendency of PT STLJ and PT AHM to perform individual optimization and the existence of disharmonization of production and distribution activities between the two companies. To solve the roots of problem, collaborative optimization and harmonization of production and distribution activities between PT STLJ and PT AHM is done by implementing a push-pull strategy involving the use of a supply hub. Improved efficiency of the production chain is measured through reduced cost of the production chain. The research methodology begins with conducting empirical and literature studies, formulating research questions, developing mathematical models, conducting trials and analyzes, and taking conclusions. The research yielded 2 (two) mathematical models, that is production chain cost model without overstocking in supply hub and production chain cost model with overstocking in supply hub. The decision variables of the two models are the size of the production lot, the lot size of the shipment, the amount of understock and overstock lot, and the number of kanban used. Each model generates a total cost of Rp199,253,000.00 and Rp214,359,000.00. Model without overstocking results in the lowest production chain cost. Both models proved to improve the inventory problems of PT STLJ. Both models resulted in decreasing inventory by 71.61% and 76.93%. Implementation requires managerial preparation in the form of procurement and selection of supply hub location, information system design for real time inventory access, and design of new standard operating procedure.